2022
DOI: 10.3390/rs14133151
|View full text |Cite
|
Sign up to set email alerts
|

Trend Changes of the Vegetation Activity in Northeastern East Asia and the Connections with Extreme Climate Indices

Abstract: In the context of global warming, vegetation activity in northeastern East Asia (40–45°N, 105–130°E) (NEA) shows a significant growth trend on a multidecadal scale, but how vegetation changes on a decadal scale is unclear. In this study, we find a significant trend of vegetation greening in northeastern East Asia during 1982–1998 and a slowdown in the greening trend during 1998–2014. Trend analysis of the extreme climate indices reveals that the trends of precipitation-related extreme climate indices are simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…Environmental adaptation determined the vegetation species composition in alpine grasslands under climate change. In recent decades, climate change increased the frequency of extreme events [29][30][31]. As the main factor to determine the distribution of biological communities, accelerated climate variations had changed the adaptability and competitiveness of different species in the ecosystem [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental adaptation determined the vegetation species composition in alpine grasslands under climate change. In recent decades, climate change increased the frequency of extreme events [29][30][31]. As the main factor to determine the distribution of biological communities, accelerated climate variations had changed the adaptability and competitiveness of different species in the ecosystem [43].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous research concluded that temperature was more important as a driving factor in vegetation growth on the QTP [22,[24][25][26][27][28]. However, since the 21st century, global warming slowdown and frequent precipitation extremes caused by atmospheric circulation made the impacts of precipitation on vegetation more concerned [29][30][31]. According to recent studies, changing precipitation patterns showed more significant effects on vegetation than annual and seasonal precipitation [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the northeastern region contains coniferous and broad-leaved forests with abundant water resources [13], where the conservative water use of forests helps mitigate the impacts of extreme heat events. The increase in the maximum temperature in high-latitude forest areas extends the growing season of plants and enhances photosynthesis, resulting in the promotion of vegetation growth [27,81].…”
Section: Impacts Of Extreme-high-temperature Events On the Ndvimentioning
confidence: 99%